2015
DOI: 10.1002/lsm.22374
|View full text |Cite
|
Sign up to set email alerts
|

Fractional laser‐assisted drug delivery: Active filling of laser channels with pressure and vacuum alteration

Abstract: Active filling with PVP secures filling of laser channels and induces a deeper, greater, more rapid delivery than conventional AFXL. This delivery technique has promise to improve treatment efficacy for medical treatments of dermally invasive lesions, such as BCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
(49 reference statements)
0
21
0
3
Order By: Relevance
“…Other techniques to enhance TDD include curettage, dermabrasion, iontophoresis, pressure waves, vacuum, and radiofrequency. Using these modalities, a myriad of medications have been successfully delivered transdermally, including triamcinolone, 5-aminolevulinic acid (5-ALA), 5-fluorouracil (5-FU), and methotrexate [5][6][7][8][9][10][11].…”
Section: Transdermal Drug Delivery (Tdd)mentioning
confidence: 99%
“…Other techniques to enhance TDD include curettage, dermabrasion, iontophoresis, pressure waves, vacuum, and radiofrequency. Using these modalities, a myriad of medications have been successfully delivered transdermally, including triamcinolone, 5-aminolevulinic acid (5-ALA), 5-fluorouracil (5-FU), and methotrexate [5][6][7][8][9][10][11].…”
Section: Transdermal Drug Delivery (Tdd)mentioning
confidence: 99%
“…Biphasic drug release is likely caused by differential powder dissolution in early and late phases. It was reported that interstitial fluid can quickly fill skin MCs after AFL treatment [34]. Patch application and firm pressing could bring lower portion of patch-coated drug powder in close contact with skin MC-filled interstitial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…To generate acoustic pressure waves the Legato II Impact (Alma Lasers Ltd., Nuremburg, Germany) was used at 70% energy intensity and 50 Hz acoustic pressure pulse rate for 12 seconds in an area of 3 × 3 cm. To generate pressure‐vacuum alterations a self‐made pressure‐vacuum‐pressure (PVP) device was used creating subsequent alternations in pressure for 3 minutes consisting of 1 minute relative positive pressure (atmospheric pressure + 1 bar), 1 minute relative negative pressure (atmospheric pressure − 0.7 bar), and relative 1 minute positive pressure (atmospheric pressure + 1 bar) based on an experimental device used by Erlendsson et al .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, relatively long application times may be needed to reach optimal drug concentrations, limiting clinical feasibility in outpatient or day care based treatments like photodynamic therapy. Furthermore, AFXL channels are believed to be filled with interstitial fluid or even a fibrin plug already shortly after AFXL treatment, preventing uptake of topical drugs in the channels . In addition, in earlier clinical trials more deeply situated skin lesions such as nodular basal cell carcinomas have failed to respond to AFXL assisted photodynamic therapy, probably due to insufficient drug uptake in the deep dermis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation